Implementation Of A* Algorithm In A Great Elephant Game With Unity 2D - Ahmad Zuhdi; Imam Ahmad; Ade Dwi Putra (Prahasta Publisher, 2023)
Video game is a game play which related to interesting User Interface through a picture which processed and transmitted into a video, as it alive and moving. At early 2014, smartphone users were increased, affected to decreasing of computer users.Pathfinding is a route search method. Google maps is one example of an application which using pathfinding method. A* Algorithm through pathfinding method is the development of dijkstra algorithm using heuristic to produce best and optimum solution. So it is possible to discover fastest path without checking in every path. Therefore, the objective of this study is implementing A* algorithm in Great Elephant game. This algorithm can be implemented to the character for discovering nearest route and increase the score easily. Because of the route is in maze form, it will be time wasting to looking for any food. This algorithm help the character to not wasting time in looking for the food. The result study is a game using A* algorithm in the player game which can access in android smartphone. The test result is using ISO 25010 in functionality suitablity aspect and produced 100% success.